A Review on the Role and Impact of Typical Alcohol Additives in Controlling Emissions from Diesel Engines - Chau, Minh Quang; Le, Van Vang; Le, Tri Hieu; Bui, Van Tam (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Today, most of the essential energy needs of humans and production are met by fossil fuels that are expected to be exhausted in the next century. Furthermore, fossil fuels are not renewable and sensitive to the environment. In particular, there is growing concerned about the negative impact of internal combustion engine emissions on climate change and global environmental pollution. Fuel and alcohol-based additives are being considered as good candidates for sustainable alternative fuels used on compression ignition engines. In this review, the different key production pathways and properties of each of the five alcohol additive candidates were discussed. Besides, their effects on the emission characteristics of diesel engines when alcohol additives are added to diesel fuel are also carefully considered. Five candidates including methanol, ethanol, propanol, butanol, and pentanol have been shown to control pollutants from combustion engines while using alcohol-based additives. This is of great significance in the strategy of coping with the threats of pollution and climate change caused by the operation of transport vehicles